SKRINING FITOKIMIA EKSTRAK ETANOL DAUN MATOA YANG BERASAL DARI PONTIANAK TIMUR DENGAN VARIASI KONSENTRASI PELARUT - Erwan Kurnianto; Ika Ristia Rahman; Hairunnisa Hairunnisa (Akademi Farmasi Yarsi Pontianak, 2021)
Matoa (Pometia pinnata J.R. Forst. & G. Forst.), a plant of the Sapindaceae family, has been widely used as traditional medicine by specific ethnic communities. Matoa leaves have pharmacological activities such as anti-diabetic, antibacterial and antioxidant. This study aims to determine the chemical content of various solvent concentrations. The solvents used in this study were ethanol 50%, ethanol 70% and ethanol 96%. The method used is a qualitative method with a colouring test. The results showed that 50% and 70% ethanolic matoa leaf extract contained flavonoids and tannins. Matoa leaf extract with 96% ethanol solvent contains secondary metabolites of flavonoids, tannins and saponins.